2016
DOI: 10.1088/1475-7516/2016/11/017
|View full text |Cite
|
Sign up to set email alerts
|

DARWIN: towards the ultimate dark matter detector

Abstract: DARk matter WImp search with liquid xenoN (DARWIN) will be an experiment for the direct detection of dark matter using a multi-ton liquid xenon time projection chamber at its core. Its primary goal will be to explore the experimentally accessible parameter space for Weakly Interacting Massive Particles (WIMPs) in a wide mass-range, until neutrino interactions with the target become an irreducible background. The prompt scintillation light and the charge signals induced by particle interactions in the xenon wil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
779
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 639 publications
(802 citation statements)
references
References 193 publications
7
779
0
Order By: Relevance
“…While these upper limits are not competitive to spindependent, elastic scattering results, as obtained by XENON100 [10] and LUX [31] (bounding the cross section to be < 1×10 −40 cm 2 , at 90% C.L., for a 100 GeV/c 2 WIMP), our results are the most stringent for the spindependent inelastic channel, and set the stage for a sensitive search of inelastic WIMP-nucleus scattering in running or upcoming liquid xenon experiments such as XENON1T [32], XENONnT [32], LZ [33], and DAR-WIN [34]. In these larger detectors, with lower intrinsic backgrounds from 85 Kr and 222 Rn decays, and improved self-shielding, the electronic recoil background will be reduced by a few orders of magnitude with respect to XENON100, and ultimately limited by solar neutrino interactions [35].…”
Section: Resultssupporting
confidence: 66%
“…While these upper limits are not competitive to spindependent, elastic scattering results, as obtained by XENON100 [10] and LUX [31] (bounding the cross section to be < 1×10 −40 cm 2 , at 90% C.L., for a 100 GeV/c 2 WIMP), our results are the most stringent for the spindependent inelastic channel, and set the stage for a sensitive search of inelastic WIMP-nucleus scattering in running or upcoming liquid xenon experiments such as XENON1T [32], XENONnT [32], LZ [33], and DAR-WIN [34]. In these larger detectors, with lower intrinsic backgrounds from 85 Kr and 222 Rn decays, and improved self-shielding, the electronic recoil background will be reduced by a few orders of magnitude with respect to XENON100, and ultimately limited by solar neutrino interactions [35].…”
Section: Resultssupporting
confidence: 66%
“…We have computed the spin independent elastic scattering cross section between DM and nucleon and have compared our results with the latest exclusion limits obtained from XENON1T and PandaX-II experiments. We have found that although some portion of σ SI − M DM plane of our present model is already ruled-out by the present direct detection experiments, there still remains sufficient region which can be tested in the near future by the different ongoing direct detection experiments like XENON1T , PandaX-II and Darwin [87]. Another test of this model would be via detection at the collider.…”
Section: Jhep08(2018)062mentioning
confidence: 62%
“…In generating these plots three parameters have been varied as shown in the figure 8). In the right panel of the same figure we show the scatter plot in the σ SI − M DM plane that can be detected in the different direct detection experiments [75,76,[85][86][87]. In the same plane we have shown the recent bound from XENON1T experiment [75] and PandaX-II experiment [76].…”
Section: Allowed Parameter Space Near Z Bl Resonancementioning
confidence: 86%
“…In the next few years, these limits are expected to be drastically lowered by experiments that will increase their total target mass and time of exposure, starting by XENONnT [94], LZ [95], and reaching the neutrino background with DARWIN [96] in ten years or so.…”
Section: Direct Detectionmentioning
confidence: 99%
“…Concerning direct detection, in the next few years XENONnT [94] and LZ [95] will push the XENON1T limit by two orders of magnitude, and within ten years DARWIN [96] will allow us to gain one extra order of magnitude. This is illustrated in figure 25.…”
Section: Jhep11(2017)132mentioning
confidence: 99%